IMPLEMENTATION OF PROBLEM BASED LEARNING (PBL) MODEL IN WRITING LEARNING OBSERVATION REPORT TEXT - Martha Boga; Shopa Riyadotul Huda; Nike Astrini (JLER (Journal of Language Education Research), 2021)
The results of the unsatisfactory teaching and learning activities become background in this study, more students get the value below the MCC, so the fact. Then it takes a proper learning model to solve the problem. Problem based learning tested as an alternative answer. The use of such learning models exert students to have problem solving skills. The purpose of this research is to know the students' learning outcomes, especially writing the observation report text using the problem based learning model. The study used a descriptive approach of the quality with a one-group pretest-postest design as a method of study used, with a population of as much as 78 students of Grade VII and took a sample of 20 students. The average result of student learning increased from 57,6 to 8I up by 23,4 points or 31.8%., and as many as 22 students received the value above the KKM. Based on the statistical test showing a sig (2-tailed) 0.003 < 0.005, there is a significant difference between the initial test and the final test which means that the problem based learning model can improve student learning outcomes.